Uterine Inversion: Management Protocol with Literature Review - Gupta, Pratiksha; Sehgal, Alka; Prasbakar, Sonil; Huria, Anju; Sahu, Ram-ji Lal (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v4i2.5029 NJOG 2010 Jan-Feb; 4(2): 3-7